2019
DOI: 10.1038/s12276-019-0268-5
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells prevent the progression of diabetic nephropathy by improving mitochondrial function in tubular epithelial cells

Abstract: The administration of mesenchymal stem cells (MSCs) was shown to attenuate overt as well as early diabetic nephropathy in rodents, but the underlying mechanism of this beneficial effect is largely unknown. Inflammation and mitochondrial dysfunction are major pathogenic factors in diabetic nephropathy. In this study, we found that the repeated administration of MSCs prevents albuminuria and injury to tubular epithelial cells (TECs), an important element in the progression of diabetic nephropathy, by improving m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 53 publications
1
42
0
Order By: Relevance
“…In diabetic animals, pathological examination shows significant glomerular mesangial expansion, matrix expansion accumulation, and basement membrane thickening [39][40][41]. Previous studies have shown that mesangial cell proliferation is responsible for observed ECM accumulation and mesangial expansion [42,43].…”
Section: Journal Of Diabetes Researchmentioning
confidence: 95%
“…In diabetic animals, pathological examination shows significant glomerular mesangial expansion, matrix expansion accumulation, and basement membrane thickening [39][40][41]. Previous studies have shown that mesangial cell proliferation is responsible for observed ECM accumulation and mesangial expansion [42,43].…”
Section: Journal Of Diabetes Researchmentioning
confidence: 95%
“…Moreover, Takemura et al showed that transplantation of ad-MSCs under the renal capsule of Spontaneously Diabetic Torii fatty rats attenuates glomerular and tubular injury to a greater extend compared to ad-MSCs administrated per intravenous route [59]. Finally, Lee SE et al have shown that treatment with ad-MSCs prevented albuminuria and tubular epithelial cell injury via induction of the Arginase-1, a marker of M2 macrophages, and subsequent improvement of mitochondrial function [60] Although these pre-clinical studies in DKD suggest that MSC-based therapy may represent a novel promising tool for DKD treatment, the experimental design of these studies is heterogeneous in terms of cell types, doses, administration route, diabetes duration, making it difficult to translate these findings into clinical practice. In addition, the use of MSCs has several limitations.…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%
“…MSCs harbor differentiation potential, immunosuppressive properties, and anti-inflammatory effects and are considered an ideal candidate cell type for the treatment of DM [32]. MSCs are found to ameliorate various diabetic complications, such as diabetic cardiomyopathy, retinopathy, nephropathy, peripheral neuropathy, and foot ulcer [33][34][35][36][37]. In our previous works, we also found that MSCs ameliorate hyperglycemia-induced endothelial injury [38,39] and diabetic kidney injury [40].…”
Section: Introductionmentioning
confidence: 95%